Mass transfer considerations for monitoring catalytic solid–liquid interfaces under operating conditions. Issue 1 (5th January 2018) - Rodríguez-García, Laura; Walker, Roland; Spier, Eyal; Hungerbühler, Konrad; Meemken, Fabian
Abstract : A combined computational and experimental approach for optimizing mass transfer in microreactors for operando ATR-IR spectroscopy characterization of catalytic solid–liquid interfaces. Abstract : Correlating catalytic performance and molecular-level information from the same catalyst sample is a promising approach to cope with the complexity of multiphase catalytic systems and to provide detailed mechanistic insight. To obtain information about the intrinsic reaction kinetics, the development of operando spectroscopy requires operation as well as surface-sensitive detection of the catalytic process in the absence of mass transfer limitations. In the present work, we investigated the effect of mass transfer on the detection of active species at the catalytic solid–liquid interface using attenuated total reflection-infrared (ATR-IR) spectroscopy. To gain a profound understanding of the mass transport within typical flow-through cells we have assessed the hydrodynamics as well as the transport of solutes within the liquid phase and the porous catalyst sample using a convection–diffusion model. The combination of computational and experimental data revealed four sensitive design parameters controlling the mass transfer within the ATR-IR spectroscopy cells. Using the asymmetric hydrogenation of phenyl cinnamic acid on a chirally modified Pd catalyst as a model reaction, we demonstrate the effects of mass transfer within the catalyst sample on the activity and selectivity.